Avaliação do processamento e propriedades de compósitos de poliuretano termoplástico reforçados com fibras silexil, em comparação com outras fibras/cargas comercialmente utilizadas - Manoel Roberio Ferreira Fernandes (2004)
The introduction of fibers/fillers in polymers is a common strategy to produce material with enhanced properties and low densities for applications such as in the automobile industry. In this work, a novel kind of an inorganic short fiber (Silexil), obtained from mineral resources, was characterized and applied as a reinforcing agent in thermoplastic polyurethane (PU). The processing and properties of PU composites having Silexil as reinforcing agent were compared with compositesproduced by using other fibers/fillers, such as: glass fibers, Lapinus fibers, wollastonite and talc. These fibers/fillers were incorporated into PU using two different routes: (1) mixing/pressing and (2) injection molding. Results showed that Silexil fibers have lower densities than other teste fibers/fillers. Silexil fibers have also similar lengths when compared to milled glass fibers. All fibers had their lengths reduced during the polymer processing operations. More aggressive processing conditions, such as longer times and higher temperatures of mixing, led to PU degradation, as observed by infrared spectroscopy. Mechanical properties of the composites showed that Silexil fibers can be usedas reinforcing agents for composites. Higher levels of reinforcement were not observed due to the following factors: degradation of fibers and PU during the process and low adhesion between fibers/fillers and polymer.